L2 attitude and motivation of secondary, undergraduate, and postgraduate ESL learners in India - Sarat Kumar Doley (Universitas Syiah Kuala, 2022)
Second language (L2) attitude and motivation-related studies focusing on differences caused by age have mostly highlighted the temporal dimension of L2 attitude and motivation. Age-related L2 motivation studies have also been gainfully employed at comparisons between L2 learners of different age groups recruited from different L2 learning environments. Such studies have not, however, attempted an analysis of the L2 attitudinal and motivational differences that may exist among L2 learners within a closer age range, e.g., 18 to 25 years. This article presents the findings of an L2 attitude and motivation survey, using a modified version of Dӧrnyei et al. (2006) and Ryan (2005), conducted among secondary, undergraduate, and postgraduate English as a second language (ESL) learners (N210) in India. It primarily presents a comparative analysis of the L2 attitudinal and motivational constructs of integrativeness, instrumentality, cultural interest, linguistic self-confidence, and L2 anxiety attested in the sample. Additionally, it offers a description of the correlation between the five L2 attitudinal and motivational constructs concerning the different ESL groups. As the ESL learners across the academic levels demonstrated ESL motivation more on the side of instrumentality, they also reported linguistic self-confidence more in the familiar environment of an L2 classroom than outside of it. Since better motivational strategies enhance learner dedication to the learning of a certain L2, an elaborated understanding of the specific differences in L2 attitude and motivation within this important age range should help design more useful and effective L2 pedagogical methods.